Bridging or fostering social distance? An analysis of penal spectator comments on Canadian penal history museums. (December 2015) - Ferguson, Matthew; Piché, Justin; Walby, Kevin
Penal history museums are among the sites where cultural meanings about prisoners and imprisonment are developed, communicated, and consumed. Little research has explored what visitors take from these encounters. Drawing on literature concerning new media communication and Brown's (2009) work on penal spectatorship, we analyze visitor comments about their sojourns into Canadian penal history sites found on TripAdvisor, a global travel website. We delve into the diverse stories that tourists share about their encounters with representations of incarceration, which we have found address the following themes: the performance of on-site actors; perceived authenticity of experiences and emotions; the convenience of visiting museums; attitudes about imprisonment; and views of penal history. Our research suggests that visits to penal history museums in Canada seldom translate into humanizing conceptions of the criminalized and views that challenge punitiveness among visitors, at least online. We also highlight how new media communications shape the actions of penal history museum workers in ways that tend to reinforce memorialization practices that foster social distance between authors and recipients of punishment.